Peningkatan Keandalan Mesin Inject Molding dengan Metode House of Risk dan Reliability Centered Maintenance - Desti Sagita Sharren Noertjahjo; Wiwin Widiasih (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The manufacturing industry must ensure the reliability of production machinery so that processes run smoothly and business objectives are achieved. If machinery is used continuously, operational disruptions can lead to breakdowns, downtime, and a decline in production performance. Such conditions can disrupt the production process and result in losses for the company. Therefore, it is important to identify and control the risks of machinery failure. The objective of this study is to identify and reduce factors that could potentially cause “breakdowns” and improve the reliability of the Sound SE 1800 machine in plastic pallet production. The House of Risk (HOR) was used to determine which risk sources should be prioritized, and Reliability-Centered Maintenance (RCM) was used to develop a maintenance plan. Research data included machine maintenance history, failure frequency, and downtime. The results of the study yielded recommendations for more efficient maintenance methods that can improve production machine performance.